Cognitive and physical markers of prodromal dementia: A 12‐year‐long population study. Issue 1 (8th January 2020) - Grande, Giulia; Rizzuto, Debora; Vetrano, Davide L.; Marseglia, Anna; Vanacore, Nicola; Laukka, Erika J.; Welmer, Anna‐Karin; Fratiglioni, Laura
Abstract: Introduction: The aim is to test whether adding a simple physical test such as walking speed (WS) to the neuropsychological assessment increases the predictive ability to detect dementia. Methods: The 2546 dementia‐free people from the SNAC‐K study were grouped into four profiles: (1) healthy profile; (2) isolated cognitive impairment, no dementia (CIND, scoring 1.5 standard deviation below age‐specific means on ≥1 cognitive domains); (3) isolated slow WS (<0.8 m/s); (4) CIND+ slow WS. The hazard of dementia (Cox regression), the positive and negative predictive values (PPV, NPV), and the area under the curve (AUC) were estimated. Results: Participants with CIND +slow WS demonstrated the highest hazard of dementia (3.4; 95% confidence interval [CI]: 2.5–4.8). The AUC increased from 0.69 for isolated CIND to 0.83 for CIND+ slow WS. Such an increase was due to the improvement of the PPV, the NPV remaining optimal. Discussion: Adding WS to the cognitive assessment dramatically increases the diagnostic accuracy of prodromal dementia.